A protopia for the Brazilian university - Naomar Almeida-Filho; Luis Eugenio Souza (Arizona State University, 2020)
From a historical-critical perspective and based on the semantic series utopia-atopy-dystopia-protopy, we analyse the "Future-se", a project presented by the Ministry of Education of Brazil for the reform of federal universities. From this perspective, firstly, we propose the characterization of two distinct models of the university, which emerged at the moment of the consolidation of the political power of the bourgeoisie, one of them being utopian and the other atopic. Secondly, we describe the historical evolution of the university in Brazil, until arriving at the "Future-se" proposal. Finally, we present an alternative proposal for university reform as part of the strategy of agglutination of forces to resist the "Future-se" and advance towards strengthening of the university as a necessary element for the sovereign, inclusive and sustainable development of the country.